Penyebarluasan Informasi Peringatan Dini Bencana Banjir di Kantor Kelurahan Kemuning Banjarbaru - Marhaeni Fajar Kurniati; Periyadi Periyadi; Ariansyah Ariansyah; Eirlin Febriana; Hernida Rahmadina (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Floods are disasters that often occur in Indonesia. Disasters caused by hydrometeorological factors always increase every year. Even though sometimes it doesn't cause many casualties, this disaster still damages infrastructure and significantly disrupts the economic stability of the community. The characteristics of floods are very diverse, floods can be caused by high rainfall without adequate soil absorption or can occur in the form of flash irrigation failures. South Kalimantan is a city known as the "City of a Thousand Rivers", which of course cannot be separated from flooding situations every rainy season. One of them is quite common in urban areas, especially the city of Banjarbaru. The dense population and the presence of rivers sometimes cause flooding, especially if the intensity of rainfall lasts long enough. Likewise, what often happens in the Kemuning Banjarbaru sub-district, floods that often come suddenly have become a normal activity for local residents. Without hesitation, there were even (9) RTs that were affected by the flash flood. Even though they are used to facing floods, especially when the rainy season arrives, residents are still advised to always be alert.